2020
DOI: 10.1200/jco.2020.38.15_suppl.101
|View full text |Cite
|
Sign up to set email alerts
|

Safety and clinical activity of gene-engineered T-cell therapy targeting HPV-16 E7 for epithelial cancers.

Abstract: 101 Background: Genetically engineered T-cell therapy has shown remarkable clinical activity in hematologic malignancies. It is not known if this type of treatment can be applied effectively to epithelial cancers, which account for 80% to 90% of human malignancies. Methods: We conducted a phase I clinical trial with a 3 + 3 dose escalation in which patients with metastatic HPV-16+ epithelial cancers were treated with a one-time infusion of genetically engineered T cells expressing a T-cell receptor targeting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Another phase I study from the NIH demonstrated a slightly better response rate with autologous TCR T cells engineered to target HPV16 E7 (response in 4/12 patients; ref. 103). The patients on the trial included five with cervical cancer, four with HNSCC, two with anal cancer, and one with vulvar cancer.…”
Section: Adoptive Cell Therapymentioning
confidence: 99%
“…Another phase I study from the NIH demonstrated a slightly better response rate with autologous TCR T cells engineered to target HPV16 E7 (response in 4/12 patients; ref. 103). The patients on the trial included five with cervical cancer, four with HNSCC, two with anal cancer, and one with vulvar cancer.…”
Section: Adoptive Cell Therapymentioning
confidence: 99%
“…Likewise, preliminary results of the Phase I study with modified T-cells were recently presented to identify the HLA-A 02:01 HPV16 E7 epitope (E7 TCR T-cells) in patients with refractory HPV16-positive tumors. 32 In the cohort of 12 patients, there were 2 patients with previously treated advanced SCCA. Both patients experienced partial responses lasting 3 and 9 months.…”
Section: Adoptive T-cell Therapiesmentioning
confidence: 99%
“…Perhaps more significant, efficacy to date in solid tumors is unimpressive and safety issues, either off- or on-target, continue to plague clinical programs ( Lu et al , 2017 ; Norberg et al , 2020 ; Parkhurst et al , 2011 ). We believe these problems are also solvable.…”
Section: Additional Challenges For T-cell Therapymentioning
confidence: 99%